Matching of Silicon Thin-Film Tandem Solar Cells for Maximum Power Output. (17th January 2013) - Ulbrich, C.; Zahren, C.; Gerber, A.; Blank, B.; Merdzhanova, T.; Gordijn, A.; Rau, U.
Abstract : We present a meaningful characterization method for tandem solar cells. The experimental method allows for optimizing the output power instead of the current. Furthermore, it enables the extraction of the approximate AM1.5g efficiency when working with noncalibrated spectra. Current matching of tandem solar cells under short-circuit condition maximizes the output current but is disadvantageous for the overall fill factor and as a consequence does not imply an optimization of the output power of the device. We apply the matching condition to the maximum power output; that is, a stack of solar cells is power matched if the power output of each subcell is maximal at equal subcell currents. The new measurement procedure uses additional light-emitting diodes as bias light in the JV characterization of tandem solar cells. Using a characterized reference tandem solar cell, such as a hydrogenated amorphous/microcrystalline silicon tandem, it is possible to extract the AM1.5g efficiency from tandems of the same technology also under noncalibrated spectra.